2013
DOI: 10.1371/journal.pone.0071929
|View full text |Cite
|
Sign up to set email alerts
|

Impedance and Electrically Evoked Compound Action Potential (ECAP) Drop within 24 Hours after Cochlear Implantation

Abstract: Previous animal study revealed that post-implantation electrical detection levels significantly declined within days. The impact of cochlear implant (CI) insertion on human auditory pathway in terms of impedance and electrically evoked compound action potential (ECAP) variation within hours after surgery remains unclear, since at this time frequency mapping can only commence weeks after implantation due to factors associated with wound conditions. The study presented our experiences with regards to initial swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 26 publications
5
47
1
Order By: Relevance
“…It might be argued that many centers postpone fitting mainly because there are reports that the impedance measurements and stimulation thresholds changed during the first weeks after surgery, although one of our previous studies revealed that the variation of impedance/electrically evoked compound action potential (ECAP) at the very beginning of insertion of electrodes implied a stable micro-environment inside the cochlea after the surgery [3]. Practically this problem can be overcome by giving patients a series of maps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be argued that many centers postpone fitting mainly because there are reports that the impedance measurements and stimulation thresholds changed during the first weeks after surgery, although one of our previous studies revealed that the variation of impedance/electrically evoked compound action potential (ECAP) at the very beginning of insertion of electrodes implied a stable micro-environment inside the cochlea after the surgery [3]. Practically this problem can be overcome by giving patients a series of maps.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid possible tissue injuries, four custom-made hooks were used to expose the cortex of the mastoid bone instead of self-retaining instruments (e.g. mastoid retractor) [3]. A thin rectangular chip of cortex bone (about 20 Â 10 Â 3 mm in size) was first harvested intact from the mastoid with a chisel, and then a drill was used for mastoidectomy ( Figure 1E).…”
Section: Surgical Procedures [3]mentioning
confidence: 99%
See 1 more Smart Citation
“…After cochlear implantation, the electrophysiological values for impedances and t-NRT drop significantly within the first 403 24 h, followed by an increase of impedance values and a secondary slow drop of the levels [Chen et al, 2013]. The process of wound healing and the foreign body reaction of the human body to the implant can last between days and weeks after implantation [Kawano et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [12] found that electrically evoked compound action potential thresholds became significantly lower measured within 24 h post-operatively as compared with intra-operatively (P \ 0.001). They concluded that it may be related to the restoration of neuronal sensitivity to the electrical stimulation, and/or the interaction between the matrix enveloping the electrodes and the electrical stimulation of the initial switch-on.…”
Section: Discussionmentioning
confidence: 99%